Society : the basics - Macionis, John J. (New Jersey : Prentice Hall, 1992)
Social Science
Keywords: Society; Culture; Socialization; Social interaction; Social stratification; Global inequality; Race; Ethnicity; Sex; Gender; Economics; Politics; Family; Religion; Education; Urbanization; Social change